Ethnoagroforestry management and soil fertility in the semiarid Tehuacán Valley, México - García-Licona, José Bernardo; Maldonado-Torres, Ranferi; Moreno-Calles, Ana Isabel; Alvaréz-Sanchéz, María Edna; García-Chávez, Juan; Casas Fernandez, Alejandro (Ethnobiology and Conservation, 2017)
Ethnoagroforestry practices and their relationship with soil fertility were studied in the semiarid Tehuacán Valley. Such practices involve management of manure, vegetation patches, wild and cultivated plants, soil, and water. This study aimed to: i) describe agroforestry management practices that influence soil fertility in maize multicultural system (milpa)-cacti forest (chichipera) AFS; ii) analyze the status of soil fertility in cultivated areas of these AFS; and iii) analyze the influence of agroforestry practices on soil nutrimental parameters of cultivated areas. In depth interviews were conducted, along with participatory tours with peasants and soil sampling in the agroforestry plots. Ethnoagroforestry practices favor adequate levels of macronutrients and organic matter in the milpa-chichipera AFS, despite Fe, Cu, and Zn deficiencies. The supply of organic matter is fundamental because it preserves soil fertility and moisture in all the plots studied. Smallholders (43%) use manure, but in irregular and insufficient way. Only 27% of interviewed people leave the land fallow for 1-2 after periods of 2-4 years of use, which does not allow the soil to reestablish fertility. Smallholders practice wild vegetation management, enabling 90% of plots to reach a high level of vegetation cover (>25%), furthermore 33% of agroforestry plots depend exclusively on this management to reestablish soil fertility. Labor force, economic conditions and plots characteristics influence agroforestry management. The amount of manure and the interaction between the agroforestry practices (vegetation cover, type of agroforestry practices, amount of manure, and fallow years) are related to the presence of N, K, Cu and B in the soil. To maintain and improve soil fertility in the milpa-chichipera AFS is important to consider local practices, biophysical conditions, and socio-economic factors.